Comparative Analysis of Clinical-Scale IFN-γ-Positive T-Cell Enrichment Using Partially and Fully Integrated Platforms - Priesner, Christoph; Esser, Ruth; Tischer, Sabine; Marburger, Michael; Aleksandrova, Krasimira; Maecker-Kolhoff, Britta; Heuft, Hans-Gert; Goudeva, Lilia; Blasczyk, Rainer; Arseniev, Lubomir; Köhl, Ulrike; Eiz-Vesper, Britta; et al. (Frontiers in Immunology, 2016)
Background and aims. The infusion of enriched CMV-specific donor T-cells appears to be a suitable alternative for the treatment of drug resistant CMV reactivation or de novo infection after both solid organ and hematopoietic stem cell transplantation. Antiviral lymphocytes can be selected from apheresis products using the CliniMACS Cytokine-Capture-System® either with the well-established CliniMACS® Plus (Plus) device or with its more versatile successor CliniMACS Prodigy® (Prodigy). Methods. Manufacturing of CMV-specific T-cells was carried out with the Prodigy and Plus in parallel starting with 0.8-1*109 leukocytes collected by lymphapheresis (n=3) and using the MACS GMP PepTivator® HCMVpp65 for antigenic re-stimulation. Target and non-target cells were quantified by a newly developed single-platform assessment and gating strategy using positive (CD3/CD4/CD8/CD45/IFN-gamma), negative (CD14/CD19/CD56), and dead cell (7-AAD) discriminators. Results. Both devices produced largely similar results for target cell viabilities: 37.2%-52.2% (Prodigy) vs. 51.1%-62.1% (Plus) CD45+/7-AAD- cells. Absolute numbers of isolated target cells were 0.1-3.8*106 viable IFN-gamma+ CD3+ cells. The corresponding proportions of IFN-gamma+ CD3+ cells ranged between 19.2% and 95.1% among total CD3+ cells and represented recoveries of 41.9%-87.6%. Within two parallel processes predominantly IFN-gamma+ CD3+CD8+ cytotoxic T-cells were enriched compared to one process that yielded a higher amount of IFN-gamma+ CD3+CD4+ helper T lymphocytes. T-cell purity was higher for the Prodigies products that displayed a lower content of contaminating IFN-gamma- T-cells (3.6%-20.8%) compared to the Plus products (19.9%-80.0%). Conclusions. The manufacturing process on the Prodigy saved both process and hands-on time due to its higher process integration and ability for unattended operation. Although the usage of both instruments yielded comparable results, the lower content of residual IFN-gamma- T-cells in the target fractions produced with the Prodigy may allow for a higher dosage of CMV-specific donor T-cells without increasing the risk for graft versus host disease.